Factors Relating To Cervical Cancer Prevention Behavior Using Visual Inspection Of Acetic Acid (IVA) In The Region Watas Marga Health Center In 2024 - Astuti, Rima Aprian; Nurjanah, Nimas Ayu Lestari; Jumita, Jumita (Universitas Dehasen Bengkulu, 2025)
The IVA Test method is one of the effective and efficient methods for early detection of cervical cancer, in addition to being cheap, it can also be done by midwives or health center officers. The percentage of coverage of early detection of cervical cancer (IVA) examinations in Indonesia is far from ideal coverage. The low coverage of IVA in cervical cancer screening efforts is the reason for the increasing development of cervical cancer. The reasons why a woman does not undergo early detection of cervical cancer are because of ignorance, feeling embarrassed if her vagina is opened by health workers, being afraid that the results of the examination are positive and not feeling the need so that she does not undergo an IVA examination. The purpose of this research was to determine the factors related to the behavior of Cervical Cancer Prevention using Visual Inspection with Acetic Acid (IVA). This research uses an analytical survey research method with a Cross Sectional approach. This research was conducted in the Watas Marga Health Center Working Area with a sample of 64 Women of Childbearing Age (WUS). The results of this research show a correlation between fear (p-value 0.040), shame (p-value 0.035), access to information (p-value 0.021) with cervical cancer prevention behavior using the IVA test at the Watas Marga Health Center in 2024. It is hoped that the Community Health Center in particular can improve its performance in socializing to the community that the IVA examination is a safe, efficient method with affordable costs so that the community is not afraid and embarrassed to take the IVA test so that the IVA examination target can be achieved and cervical cancer cases can be detected immediately.